Indonesian Big Agrarian Data: A Contextual-Based Interpretive Structural Model - Elham, Elham; Maarif, Syamsul; Anwar, Syaiful; Mardiana, Rina (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
The government neglects to pay attention to village development as a result of the inaccurate data collected by numerous entities. Whereas in reality, there are many people who currently hold land tenure that might be used to grow into a community that is sustainable. This study therefore intends to evaluate the Indonesian Big Agrarian Data (IBAD) implementation paradigm based on sustainable villages. The study was carried out in the West Nusa Tenggara village of Senawang in the Orongtelu District of Sumbawa Regency. Six months were spent conducting the research. The information used is a combination of primary data from questionnaire and secondary data from earlier studies or library searches. The ISM analysis approach was employed to develop a sustainable village implementation model. The findings indicate that proper implementation can impact the community, BPN/ATR, and BIG by utilizing licensed surveyors and focusing on policy interpretation from the Coordinating Ministry for the Economy. However, there is no complete data survey and map method, and a data guardian has not been established. Therefore, adjustments are necessary to develop comprehensive village measurement policies and change employee perspectives.